Developing a Model for Iran’s Military Export Pathology (Case: One of the Iranian Military Holding Corporations) - Gholamreza Tavakoli; Mehdi Elyasi; Maysam Shafiee Roodposhti; Aliasghar Heidari (مطالعات مدیریت بهبود و تحول, 2011)
One of the most important strategic sectors of any country's economyis the military sector.Thus governments allocate a considerable amount of effort and cost to helpthis sector through obtaining its objectives. Meanwhile, it is known that aneffective way for military sectors to cover their own expenditures, andshowcase their powers, is export. Also, it is known that a major prerequisitefor prospering in exports is acknowledging the customer wants and fulfillingthem.This article tries to identify the harms of Iran’s military export, and employsthe qualitative methods such as open questionnaire, depth interview, andcontent analysis. Afterwards, its conceptual model is drawn making use ofthe affinity diagram. At the final stage, using quantitative methods, harmsare categorized and prioritized by the results acquired from the adaptivematrix. Statistical population of this research is comprised of 63 internalexperts (with 0.65 cooperation ratio) and 95 foreign experts (with 0.65cooperation ratio). Findings revealed that internal experts found 9 harmitems to be critical, needing urgent investigation and resolution, whilethis number was 4 with the foreign experts.